2023
DOI: 10.1002/jssc.202300060
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantitative analysis of the chemical constituents of Gandouling tablets using ultra‐high‐performance liquid chromatography with quadrupole time‐of‐flight mass spectrometry

Abstract: Gandouling tablets are used in a clinical agent for the treatment of hepatocellular degeneration; however, their chemical constituents have not been elucidated. Here, we screened and identified the chemical constituents of Gandouling tablets using ultra-high-performance liquid chromatography (UHPLC)-quadrupole time of flight/mass spectrometry. A method for the quality evaluation of Gandouling tablets was developed by combining the UHPLC fingerprints and the simultaneous quantitative analysis of multiple active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…In recent years, liquid chromatography-mass spectrometry (LC-MS) has been increasingly used in the analysis of components in traditional Chinese medicine [9]. Moreover, an increasing number of scholars were adopting ultra-high-performance-liquid chromatography quadrupole-orbitrap-mass spectrometry (UHPLC-Q-Orbitrap-MS) to identify and analyze unknown herbal medicines in compound prescriptions [10][11][12]. Jang et al [13] used UHPLC-Q-Orbitrap-MS to qualitatively analyze the main components of Jin Mu Tang, and 23 compounds were identified and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, liquid chromatography-mass spectrometry (LC-MS) has been increasingly used in the analysis of components in traditional Chinese medicine [9]. Moreover, an increasing number of scholars were adopting ultra-high-performance-liquid chromatography quadrupole-orbitrap-mass spectrometry (UHPLC-Q-Orbitrap-MS) to identify and analyze unknown herbal medicines in compound prescriptions [10][11][12]. Jang et al [13] used UHPLC-Q-Orbitrap-MS to qualitatively analyze the main components of Jin Mu Tang, and 23 compounds were identified and characterized.…”
Section: Introductionmentioning
confidence: 99%
“…(Ezhu, EZ), which was approved by Anhui Food and Drug Administration as the hospital preparation of the First Affiliated Hospital of Anhui University of Traditional Chinese Medicine in 2005 (Zhang et al., 2022 ). Early studies have shown the positive effects and mechanisms of GDL in the treatment of WD liver injury (Cheng et al., 2023 ; Liu et al., 2023 ; Zhang et al., 2021 ). Its protective effect on nerve injury has been proved in previous clinical, animal, and cell model studies (Dong et al., 2021 ; Zhang, 2019 ; Zhang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%